The Effects of Transfer Pricing and Thin Capitalization on Tax Aggressiveness in Multinational Companies - Annisa Fitri Anggraeni; Ai Lastari (Dinasti Accounting Review, 2026)
The increase in nominal tax revenue has not been accompanied by an increase in the tax ratio. The low tax ratio indicates the presence of tax avoidance in Indonesia. Some tax avoidance practices that can be employed include transfer pricing and thin capitalization. This study aims to identify and empirically test the effects of thin capitalization and transfer pricing on tax aggressiveness. The data used in this study are secondary data. This study uses a sample of companies in the Primary Consumer Goods (Consumer Non-Cyclicals Goods) sector listed on the Indonesia Stock Exchange from 2022 to 2023. The population of the study consists of 89 companies observed over a two-year period. This study employs a purposive sampling method. The total sample for this study comprises 178 financial statements. The data analysis techniques used include descriptive statistical analysis, estimation of panel data regression models, panel data regression model selection techniques, hypothesis testing, and the coefficient of determination, utilizing the Eviews 13 software. The results of this study indicate that, partially, transfer pricing has a negative and significant effect on tax aggressiveness, and similarly, thin capitalization has a negative and significant effect on tax aggressiveness. Simultaneously, transfer pricing and thin capitalization together have a significant effect on tax aggressiveness.